2007
DOI: 10.1002/mawe.200700189
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity issues of EB‐PVD thermal barrier coatings

Abstract: The thermal conductivity of electron-beam physical vapor deposited (EB-PVD) thermal barrier coatings (TBCs) was investigated by the Laser Flash technique. Sample type and methodology of data analyses as well as atmosphere during the measurement have some influence on the data. A large variation of the thermal conductivity was found by changes in TBC microstructure. Exposure at high temperature caused sintering of the porous microstructure that finally increased thermal conductivity up to 30 %. EB-PVD TBCs show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…the columns all grow through and do not change in thickness or number at this interface. This is identical to findings for 7YSZ layers that were originating from three separate interrupted runs [33] where columns grew through from one layer to the next without any interruption. Only minor variations in porosity were found in this study at the interface regions.…”
Section: Discussionsupporting
confidence: 86%
“…the columns all grow through and do not change in thickness or number at this interface. This is identical to findings for 7YSZ layers that were originating from three separate interrupted runs [33] where columns grew through from one layer to the next without any interruption. Only minor variations in porosity were found in this study at the interface regions.…”
Section: Discussionsupporting
confidence: 86%
“…(4) It exists a correlation between the chamber pressure and composition change during deposition. 5,24 The change in vapor pressure during deposition probably turns out to affect heavily the chamber pressure leading to deviate of composition. (5) The melting and evaporation behavior of the source material, ingot density, deposition rate and efficiency, gun power, e-beam focus, dwell time, chamber pressure and vapor cloud geometry are predominant factors to control the coatings' composition during deposition.…”
Section: Composition Of the Coatingmentioning
confidence: 99%
“…The thermal conductivities of EB-PVD coatings decrease slightly with increasing temperature. It was reported that thermal conductivity of partially yttria-stabilized zirconia (P-YSZ) EB-PVD coatings decreased with increasing temperature [14]. In addition, it is apparent that the thermal conductivities of the coatings are remarkably lower than those of the sintered samples.…”
Section: Thermophysical Propertiesmentioning
confidence: 98%
“…Some investigations have already been reported regarding the relationship between the thermal conductivity and the microstructure of TBCs [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%